Trends in Influenza Vaccination Rates in Participants With Airflow Limitation: The Korea National Health and Nutrition Examination Survey 2007–2018 - Lee, Hyun; Choi, Hayoung; Jo, Yong Suk (Frontiers in Medicine, 2022)
Background: Influenza vaccination is strongly recommended for people with chronic lung diseases, including chronic obstructive pulmonary disease, to reduce risk of exacerbation. We assess the influenza vaccination rate and its related factors in participants with airflow limitation (AFL) using nationally representative data in Korea. Methods: We conducted a cross-sectional study from the Korea National Health and Nutrition Examination Survey from 2007 to 2018. Individuals ≥ 40 years who underwent spirometry and had identifiable information on influenza vaccination status were included. Results: Overall influenza vaccination coverage was 61.2% in participants with AFL and 41.8% in participants without AFL. Age had a significant impact on the yearly vaccination rate in participants with AFL. Over the 10 years of study period, while the yearly vaccination rate steadily increased from 58.3% to 61.9% in elderly participants (≥65 years) with AFL (p for trend = 0.117), the yearly vaccination rate decreased from 41.5% to 30.8% in younger participants (<65 years) (P for trend = 0.038). In multivariable analyses, younger age (adjusted odds ratio [OR] for unvaccinated = 0.88, 95% CI = 0.87–0.90), male (adjusted OR = 1.64; 95% CI = 1.23–2.19), and current smokers (adjusted OR = 1.42, 95% CI = 1.01–2.00) were associated with increased odds of being unvaccinated. Conclusions: The vaccination rate in participants with AFL affected by age. Younger age, male sex, and current smoking were associated with unvaccinated status. More attention and targeted interventions are required to improve the influenza vaccination rate in those with AFL.